Strange curves, counting rabbits, and other mathematical explorations - Ball, Keith M., 1960- (Princeton University Press, 2003)
"In Strange Curves, Counting Rabbits, and Other Mathematical Explorations, Keith Ball draws on areas of mathematics from probability theory, number theory, and geometry. He explores a wide range of concepts, some more lighthearted, others central to the development of the field and used daily by mathematicians, physicists, and engineers." "Accessible to anyone with basic calculus, this book is a treasure trove of ideas that will entertain, amuse, and bemuse students, teachers, and math lovers of all ages."--Jacket